Application of remote sensing in the identification of the geological terrain features in Cameron Highlands, Malaysia - Abd Manap, Mohamad; Ramli, Mohammad Firuz; Sulaiman, Wan Nor Azmin; Surip, Noraini (Penerbit Universiti Kebangsaan Malaysia, 2010)
The geological terrain mapping conducted by the Department of Mineral and Geosciences, Malaysia (JMG) is time-consuming especially for inaccessible or remote area. In order to improve the current practice, remotely sensed data such as aerial photographs and Landsat imagery were used to identify geological terrain features in Cameron Highlands, Pahang. It was found that features such as hillcrest, sideslope, footslope, straight slope, convex slope and concave slope were easily delineated using aerial photographs draped over a digital elevation model (DEM) compared to using Landsat imagery.